Study on the difference of chemical composition of insulator contamination on UHV‐AC and ‐DC transmission lines. Issue 1 (1st January 2018) - Li, Lee; Jiang, Yunpeng; Lu, Ming; Liu, Zehui; Hua, Kui; Li, Zhe
Abstract : For the ultra high voltage (UHV)‐DC and UHV‐AC transmission lines, their contamination characteristics are different. Thus, researching the contamination polluted degree of UHV‐AC and UHV‐DC lines by geoaccumulation index and enrichment factor method is an ingenious method. This study analyses and compares the chemical composition of contamination on parallel energised UHV‐DC (800 kV) and UHV‐AC (1000 kV) overhead transmission lines. The results indicate that the major cations of insulator contamination are Ca 2 +, and NH4 +, and the major anions of insulator contamination are SO4 2− and NO3 − both on UHV‐DC and UHV‐AC lines. For the UHV‐DC line, the concentrations of the same cations on the insulator bottom surface are higher than that of on the top surface. However, on the UHV‐AC line, the same cation concentrations on the bottom surface close to the one on the top surface. The metallic elements of Ca 2+ and Zn 2+ are in seriously polluted degree. Also, the polluted degree of contamination on UHV‐DC insulator is more serious than UHV‐AC insulator. This study considers that field charging plays an important role in accumulating contamination.